THE EFFECT OF TEMPERATURE DEPENDENCE ON TIN PEROVSKITE SOLAR CELL USING SCAPS 1D - Ukwenya, Jessica Amuchi; Owolabi, Joshua Adeyemi; Onimisi, Mohammed Yusuf; Danladi, Eli; Udeh, Samuel Michael; Ushiekpan, Ugbe Raphael (FUDMA JOURNAL OF SCIENCES, 2023)
Perovskite solar cell (PSC) has become a force to reckon with in the renewable energy community because of its performance and low cost of production. Solar energy is one of the most demanding renewable sources of electricity. Electricity production using photovoltaic technology, not only helps meet the growing demand for energy, but also contributes to mitigate global climate change by reducing dependence on fossil fuels. Simulation is based on a mathematical design that describes the system. Numerical simulation technique of solar cells devices has over the years proven to be a viable tool for observing and understanding the properties of solar cell devices such as the optical, electrical and mechanical properties of complex solar cell devices. It also helps to reduce processing cost and time spent on solar cell device fabrication by providing useful information on how to vary the production parameters to improve the device performance. Solar cell capacitance simulator in one dimension (SCAPS-1D) was used in the modeling and simulation of sandwiched perovskite solar cells (PSCs) with a planar hetero-junction structure in the arrangement of the sandwiched model (FTO/CdS/CH3NH3SnI3/HTM). The energy band diagram, I-V characteristics and other parameters was obtained. The configuration for better performance was then determined, from which further simulations were carried out. When the operating temperature was varied the result shows an overall efficiency of 24.25%, FF of 82.80%, JSC of 30.73mA/cm2, VOC of 0.95V was obtained.
Keywords: Perovskite Solar Cell; numerical simulation; SCAPS; conversion efficiency; ETM